Le rôle des collectivités territoriales dans l’adaptation des enjeux environnementaux globaux à l’échelle locale - Véronique Van Tilbeurgh; Laurence Le Dû-Blayo (VertigO)
Environmental stakes, as defined by public policies, result in developments in rural space, confronting local societies to transformations of their close environment. The article aims at explaining the process through which global stakes, such as the struggle against climatic change and the protection of biodiversity, are converted into local stakes through the action of local political structures. Two main factors determine the perception of these stakes by the population : the structure of local societies, and the degree of adaptability of these developments.The communication is based on the comparison of different developments (two Aeolian parks and two pedestrian paths). In all cases, the public debate has been organised by local political structures to adapt the developments to the stratification of local societies and to the local power stakes.